Implementasi Kebijakan Retribusi Parkir Badan Jalan di Kota Pekanbaru - Lubis, Ema Fitri; Sundari, Rio; Rosmayani, Rosmayani; Rahmi, Zilfi Purnama (Universitas Tribhuwana Tungga Dewi, 2024)
In urban areas with high levels of mobility in driving, the high push for urbanization and the rapid demand for vehicles have resulted in additional parking spaces. Parking management policies play a major role in developing strategies to improve mobility in urban areas in Indonesia. One of these cities is the kota Pekanbaru. This research aims to analyze what factors hinder the implementation of the on-street parking levy policy in Pekanbaru City. The method used in this research is descriptive qualitative, collecting data by means of interviews, observation and documentation. The research results show that research using indicators of size and policy objectives is in the category of not running well in relation to the determined tariff rates. In terms of resources, the facilities and services received by parking users are felt to be less than optimal. The characteristics of implementing agents include obstacles such as weak supervision carried out by the kota Pekanbaru parking UPT. Indicators of attitudes or tendencies of implementers include coordination between the Transportation Service and UPT. Parking as a technical implementer, parking attendant and involving partners, namely the third-party PT. Yabisa Sukses Mandiri (YSM). Indicators of communication between organizations and implementing activities are felt to be less than optimal in providing services to parking service users. However, in terms of policy implementation activities, it has gone well. Furthermore, the economic, social and political environmental indicators have been running well in terms of economic carrying capacity, but in terms of the socio-political environment it has not been running optimally.Pada wilayah perkotaan dengan tingkat mobilitas dalam berkendara, tingginya dorongan urbanisasi serta pesatnya permintaan kenderaan, menimbulkan penambahan ruang parkir. Kebijakan manajemen parkir berperan besar dalam menyusun strategi untuk memperbaiki mobilitas di perkotaan di Indonesia. Salah satu kota tersebut adalah Kota Pekanbaru. Penelitian ini bertujuan untuk menganalisis faktor apa saja yang menjadi penghambat dalam implementasi kebijakan retribusi parkir badan jalan di Kota Pekanbaru. Metode yang digunakan dalam penelitian ini adalah deskriptif kualitatif, pengumpulan data dengan cara wawancara, observasi, dan dokumentasi. Hasil Penelitian menunjukkan bahwa penelitian menggunakan ndikator ukuran dan tujuan kebijakan berada pada kategori belum berjalan dengan baik terkait besaran tarif yang sudah ditentukan. Dari segi sumber daya sumber daya fasilitas dan layanan yang diterima pengguna parkir dirasakan kurang maksimal,. Karakteristik agen pelaksana terdapat kendala seperti lemahnya pengawasan yang dilakukan UPT perparkiran Kota Pekanbaru. Indikator sikap atau kecenderungan para pelaksana adanya koordinasi antara Dinas Perhubungan dan UPT. Perparkiran sebagai pelaksana teknis, juru parkir serta melibatkan mitra yakni pihak ketiga PT. Yabisa Sukses Mandiri (YSM). Indikator komunikasi antar organisasi dan aktivitas pelaksana dirasakan kurang optimal dalam memberikan pelayanan kepada pengguna jasa layanan parkir. Namun dalam hal aktivitas pelaksana kebijakan sudah berjalan dengan baik. selanjutnya indikator lingkungan ekonomi, sosial, dan politik sudah berjalan dengan baik dari segi daya dukung ekonomi, namun dalam hal lingkungan sosial politik belum berjalan optimal.